STRATEGI PEMENANGAN PDI PERJUANGAN PADA PILKADA KOTA SEMARANG TAHUN 2015 (Studi Kemenangan Hendi – Ita) - aji, erry bismono; ., Susilo Utomo; ., fitriyah . (Journal of Politic and Government Studies, 2017)
ABSTRACTThis study analyzed the political strategies used by the Partai Demokrasi Indonesia Perjuangan (PDI-P) of Semarang in the Semarang Mayor Election 2015. In that election, PDIP carried its main cadres, Hendrar Prihadi and Hevearita Gunaryanti Rahayu whiched have good relationship with PDI Perjuangan in Semarang. PDI Perjuangan became the main bearer party candidate pairs, although Partai Nasdem and Partai Demokrat who joined coalition. And then, what about PDI Perjuangan political strategy in the Semarang Mayor and Deputy Mayor Election 2015, in order to be able to win te vote? PDI Perjuangan has a big adventage, because in semarang is a huge base mass PDI Perjuangan. Semarang City is often reffered to as house of bull. But must be remembered that the other opponents candidate is a strong opponent and has influence in Semarang too. The researched used qualitative methode to understand and describe how PDI Perjuangan politic strategy to win Semarang Mayor Election 2015. The data were obtained through interviews with all they supporting team and PDI Perjuangan cadres who were involved in the process of succeeding Hendi-Ita in the Semarang Mayor Election 2015. As well the data obtained from documents. Political strategies that were used by Partai Demokrasi Indonesia Perjuangan in Semarang Mayor election 2015, conducted in the form of political campaign strategy, Image/Figure strategy, the mass-base strategy, strategy carries the name of a popular cadres, community approach strategy and general strategy. The strategies combination eventually could make Hendi-Ita win the election with 370,237 votes or 46.36% of the vote. Hendi-Ita beat the other candidate Marmo-Zuber and Sigit-Bagus each with 220,745 votes for Marmo-Zuber or 31.49% and 149,712 votes for Sigit-Agus or 21.74% of the vote.Keywords: Mayor Election, Partai Demokrasi Indonesia Perjuangan, Political Strategy.